2016
DOI: 10.1103/physrevb.94.075148
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ground state ofSr2IrO4and implications for second-harmonic generation

Abstract: The currently accepted magnetic ground state of Sr2IrO4 (the − + +− state) preserves inversion symmetry. This is at odds, though, with recent experiments that indicate a magnetoelectric ground state, leading to the speculation that orbital currents or more exotic magnetic multipoles might exist in this material. Here, we analyze various magnetic configurations and demonstrate that two of them, the magnetoelectric − + −+ state and the non-magnetoelectric + + ++ state, can explain these recent second-harmonic ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 54 publications
(160 reference statements)
3
33
0
Order By: Relevance
“…In order to compare iridium fluorides and iridates, we have expressed the experimental results presented above in terms of single-ion model parameters, such as the effective trigonal distortion ∆ of the cubic crystal field, and the spin-orbit-coupling constant ζ, often used in the literature of iridates 2, 43,44,[48][49][50][51][52][53][54][55] . By constraining the energies of the j eff = 3/2 excited states as calculated from the single-ion model to the energy positions of the features A and B, and by taking into account the sign of the octahedral distortion as determined by XRPD, we estimated the values of ∆ and ζ for our systems.…”
Section: Resultsmentioning
confidence: 99%
“…In order to compare iridium fluorides and iridates, we have expressed the experimental results presented above in terms of single-ion model parameters, such as the effective trigonal distortion ∆ of the cubic crystal field, and the spin-orbit-coupling constant ζ, often used in the literature of iridates 2, 43,44,[48][49][50][51][52][53][54][55] . By constraining the energies of the j eff = 3/2 excited states as calculated from the single-ion model to the energy positions of the features A and B, and by taking into account the sign of the octahedral distortion as determined by XRPD, we estimated the values of ∆ and ζ for our systems.…”
Section: Resultsmentioning
confidence: 99%
“…The former may be a platform of topological superconductivity, 41,45,46,48) and the latter is parity-violating electromagnetic order. Experimental study traces back to magnetic monopole order in Cr 2 O 3 , 64) and recent studies found magnetic toroidal order in LiCoPO 4 , 65,66) magnetic quadrupole order in Sr 2 IrO 4 67,68) and Ba(TiO)Cu 4 (PO 4 ) 4 , 69) and odd-parity electric order in Cd 2 Re 2 O 7 . 70,71) Recent theoretical study has also identified magnetic hexadecapole order in BaMn 2 As 2 .…”
Section: Introductionmentioning
confidence: 81%
“…Another topic of recent interest in locally NCS crystals is an odd-parity electromagnetic multipole order [25,28,[32][33][34][35][36][37][38][39][40][41][42][43], which spontaneously breaks global inversion symmetry through an anisotropic spin and charge distribution. Although previous studies provided a profound understanding of evenparity multipole order in strongly correlated electron systems [44][45][46][47], it has been recently recognized that odd-parity electromagnetic multipole order is ubiquitous in materials.…”
Section: Introductionmentioning
confidence: 99%